Live attenuated influenza A virus vaccine expressing an IgA-inducing protein protects pigs against replication and transmission - Rajao, Daniela S.; Zanella, Giovana C.; Wymore Brand, Meghan; Khan, Shehroz; Miller, Michael E.; Ferreri, Lucas M.; Caceres, C. Joaquin; Cadernas-Garcia, Stivalis; Souza, Carine K.; Anderson, Tavis K.; Gauger, Phillip C.; Vincent Baker, Amy L.; et al. (Frontiers in Virology, 2023)
The rapid evolution of influenza A viruses (FLUAV) complicates disease control for animal and public health. Although vaccination is an effective way to control influenza, available vaccines for use in swine result in limited protection against the antigenically distinct FLUAV that currently co-circulate in pigs. Vaccines administered parenterally usually stimulate IgG antibodies but not strong mucosal IgA or cell-mediated responses, which are typically more cross-reactive. We developed a live attenuated influenza virus (LAIV) vaccine containing IgA-inducing protein (IGIP) as a molecular marker and immunomodulator. This Flu-IGIP vaccine was tested in a bivalent formulation (H1N1 and H3N2) against challenge with antigenically drifted viruses in pigs. Pigs were vaccinated intranasally with either a bivalent Flu-IGIP or a bivalent Flu-att (control without IGIP) and boosted two weeks later. Three weeks post boost, pigs were challenged with antigenically drifted H1N1 or H3N2 virus. Vaccinated pigs had increased numbers of influenza-specific IgA-secreting cells in PBMC two weeks post boost and higher numbers of total and influenza-specific IgA-secreting cells in bronchoalveolar lavage fluid (BALF) 5 days post inoculation (dpi) compared to naïve pigs. Pigs vaccinated with both Flu-IGIP and Flu-att shed significantly less virus after H1N1 or H3N2 challenge compared to non-vaccinated pigs. Vaccination with Flu-att reduced respiratory transmission, while Flu-IGIP fully blocked transmission regardless of challenge virus. Both Flu-IGIP and Flu-att vaccines reduced virus replication in the lungs and lung lesions after inoculation with either virus. IgG and IgA levels in BALF and nasal wash of vaccinated pigs were boosted after inoculation as soon as 5 dpi and remained high at 14 dpi. Our results indicate that Flu-IGIP leads to protection from clinical signs, replication and shedding after antigenically drifted influenza virus infection.